Designing Non‐Native Iron‐Binding Site on a Protein Cage for Biological Synthesis of Nanoparticles. Issue 15 (2nd May 2014) - Peng, Tao; Paramelle, David; Sana, Barindra; Lee, Chiu Fan; Lim, Sierin
<x xml:space="preserve">Abstract</x> In biomineralization processes, a supramolecular organic structure is often used as a template for inorganic nanomaterial synthesis. The E2 protein cage derived from Geobacillus stearothermophilus pyruvate dehydrogenase and formed by the self‐assembly of 60 subunits, has been functionalized with non‐native iron‐mineralization capability by incorporating two types of iron‐binding peptides. The non‐native peptides introduced at the interior surface do not affect the self‐assembly of E2 protein subunits. In contrast to the wild‐type, the engineered E2 protein cages can serve as size‐ and shape‐constrained reactors for the synthesis of iron nanoparticles. Electrostatic interactions between anionic amino acids and cationic iron molecules drive the formation of iron oxide nanoparticles within the engineered E2 protein cages. The work expands the investigations on nanomaterial biosynthesis using engineered host‐guest encapsulation properties of protein cages.